Analysis of Difficulty Level on The Topic Line and Angle - Kleden, Maria Agustina; Lobo, Maria; Lapenangga, Ganesha; Sugi, Yosep (Universitas Sebelas Maret, 2020)
A study on the level of difficulty of the mathematics subject has been carried out inthe Junior High Schools Aroun the City of Kupang. The samples were taken purposively among year 8 students and their mathematics teachers in the second semester from 8 public schools and 5 private schools. The number of samples was 659 students and 33 teachers. The analysis was conducted on the topics of Comparison, Aritmatic, Lines and Angles and Triangles and Quadrilateral Shapes. The study shows that the most challenging mathematic topics for the year 8 students in the City of Kupang is Lines and Angles followed by the calculation of area of irregular plane shapes particularly on pentagon forms